Pengaruh Sustainability Reporting terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Mediasi: Studi Empris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Faridzan, Muhammad Nadhif; Fitra, Halkadri (Universitas Negeri Padang, 2025)
The large number of companies with below-standard firm values indicates a lack of investor confidence in mining companies in recent years. Meanwhile, during the same period, companies were also required to report a sustainability report based on the Financial Services Authority Regulation (POJK) No. 51/POJK.03/2017. This study aims to determine the effect of sustainability reporting on firm value with financial performance as a mediating variable, conducted on mining companies in the period 2021–2024. This research is a quantitative study using secondary data, with 87 mining company samples after outlier removal, which were then processed using the SmartPLS 4 application. The results show that sustainability reporting does not have a significant effect on firm value, while financial performance cannot mediate the relationship between sustainability reporting and firm value. It is suggested that future research increase the number of samples, consider adding other independent variables that may significantly affect firm value, and modify or complement the measurements of financial performance and firm value with alternative indicators.